(untitled) (Al-Qamar, 2021)
Islam is a complete way of life. All human needs have been regarded. One of them is recreation. Recreation is the important necessity of human being. Everybody needs physical and mental recreation so that his physical and mental energies may be used in a positive way. Women are no exception. In fact, they need more energy as they have to take care of whole family. Unfortunately, our females are engaged in unhealthy and forbidden activities in the name of “recreational activities”, which are not aligned with our religious, social and cultural values. This paper deals with the challenges of these activities of Muslim women in the light of Sīrah. Author has presented the guidelines of Quran and Sunnah regarding entertainment and recreation of women.